Esclerose múltipla e imagens de Deus: a influência da crença na qualidade de vida de portadores/as da doença - Amoroso, Gina Corsi (2009)
The Multiple Sclerosis (MS) is a progressive disease, with no cause and no cure. The health professionals who treat MS people have as a principal role improve their quality of life. By relieving theirs symptoms, getting patient emotionally stronger to help them cope with their disabilities and help then to find better solutions to adapt with physical, emotional and social impairments. As MS has no cause and no cure the MS people can use the religion beliefs as a important tool to cope with MS .Because they can find in religion same reasons for having MS, consolation and courage to deal with theirs impairment . This study has the objective to know the MS people religious beliefs to analyze how it influence in quality of life their quality of life. Methods; open interviews, were used to find out about the religious beliefs and questionnaires Functional Assessment of Multiple Sclerosis (FAMS) and The spiritual/ religious Coping,(SRC) were used to measure their quality of life and the way MS people use their faith to cope with stress. The result show that there is a statistic significant relation between FAMS and SRC. And the type of religious beliefs does not influence in the quality of life. Conclusion; The religions beliefs of MS people in this study showed rich and varied and meaningful and the way that this people can use their faith to cope with stress situations can influence in their quality of life